Challenges in strategic facilities management : analysis of problems faced by university facilities managers in New Zealand and Australia : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy (PHD) in Construction, School of Engineering & Advanced Technology, College of Sciences, Massey University, November 2014 - Kamarazaly, Myzatul Aishah (Massey University, 2014)
Like any set of professionals, the facilities managers (FMgrs) in universities face several challenges that constrain performance of their crucial roles. These range from internal managerial issues to external constraints which can be structured as PESTELI (i.e. political, economic, socio-cultural, technological, environmental, legal and institutional) constraints. The literature is replete with inexhaustible list of the challenges. However, a major gap in the literature is the lack of clear indications of the risk levels attached to these challenges or extent of their impact on the performance of the FMgrs. This study therefore aimed to contribute to filling this knowledge gap by exploring in depth the challenges and their relative levels of influences on the performance of university FMgrs. The specific objectives of the study were four-fold: (i) to identify the current internal and external challenges faced by universities facilities managers; (ii) to analyse the risk levels of the identified challenges based on their relative levels of impact on the achievement of the university strategic FM goals and their occurrence frequencies; (iii) to establish some innovative measures for addressing the key challenges; and (iv) to determine the key challenges facing tomorrow’s university facilities managers. Using the descriptive survey method, the study focused on the facilities managers in the Australasian universities. These comprised eight universities in New Zealand and forty universities in Australia. Views of facilities managers in these universities were obtained during three stages of data gathering: qualitative data gathering at the pilot interview stage, quantitative data gathering at the questionnaire survey stage, and some case studies at the model test survey stage. Descriptive statistics, multi-attribute analysis, rank correlation tests and statistical tests of significance were employed in the analysis of the research data and the tests of research hypotheses. Results showed that the critical challenges facing the university facilities managers (UFMs) comprised issues relating to the following: finance-related current internal challenge, economic-related current external challenges and sustainability-related future challenges. Overall, poor funding was identified as the root of all other issues faced by the UFMs, hence majority of the suggested strategies for addressing the key challenges related largely to financial improvement measures. Other key measures included optimizing asset utilization, supporting business case for capital investment with demonstrable returns on investment, improving FM’s strategic relevance through linking FM and corporate strategies, and investment in efficient technologies such as the building automation and management systems. The findings have contributed to filling an important knowledge gap by not only identifying the current and future challenges facing the UFMs, but also prioritising them based on their relative influences on the achievement of the strategic goals of the FM departments. This way, the limited resources at the disposal of the UFMs could be disbursed more cost-effectively in addressing the critical challenges in line with their identified risk levels. This would be of practical benefit to the facilities and property managers in formulating appropriate responses to the identified critical constraints with a view to achieving more satisfactory outcomes in their operations. Keywords: Australasia, challenges, facilities managers, risk analysis, strategic facilities management, university facilities.
Keywords: College facilities; University facilities; Management; Facility management; New Zealand; Australia; Australasia; Challenges; Facilities managers; Risk analysis; Strategic facilities management